HOW HAS THE COVID-19 PANDEMIC AFFECTED THE REAL AND MONETARY SECTORS IN INDONESIA? - Patria Yunita (Journal of Islamic Monetary Economics and Finance, 2021)
This study aims to find empirical evidence for the effects of the Covid-19 pandemic on the Indonesia real and monetary sectors. The real sector condition is represented by fluctuations in the farmer exchange rate in ten provinces; this rate has direct and indirect effects on farmers’ welfare. On the other hand, the condition of the monetary sector is illustrated by shifts in the consumer confidence index due to fluctuations in Islamic and conventional financial system indicators. We used a panel regression model to examine the farmer exchange rate and a binary logistic regression model to examine the consumer confidence index. The results statistically demonstrate that the pandemic conditions have affected both the real sector and the consumer confidence index of the Islamic financial sector. However, the pandemic has not affected the consumer confidence index of the conventional financial sector. This phenomenon exists because of the speculative action from conventional investors in taking risks and opportunities, which are forbidden in the Islamic context. The indicator which shifts the conventional consumer confidence index is the composite stock index (IHSG), while the Islamic consumer confidence index is shifted by changes in the Islamic money market rate, the Jakarta Islamic index and the Islamic banking capital ratio. Our empirical findings conclude that, in such a critical situation, the behaviour of conventional and Islamic consumers is totally different, thus influencing consumer confidence in each sector.